Potensi Ekstrak Kecambah Kacang Hijau (Phaseolus aureus) untuk Meningkatkan Viabilitas Spermatozoa akibat Paparan Monosodium Glutamat (MSG) - Endah Mulyani; Artika Uthary; Rusdiyana Ekawati; Farida Nur’aini; Sulasthia; Dyah Eka Kurniawati; Nastiti Trikurniadewi (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
Monosodium Glutamate (MSG) as an additional ingredient to enhance food taste has a negative impact on mice spermatozoa. This research aims to explore the potential of mung bean sprout extract as a therapeutic ingredient to increase the viability of mice spermatozoa exposed to a toxic dose of MSG (4 mg/g BW) for 35 days. This research was an experimental study with 5 experimental groups, namely a positive control group and a negative control group as well as 3 therapy groups with doses of mung bean sprout extract of 0,1 g, 0,2 g, dan 0,4 g peroral for 15 days.. The results of the ANOVA test showed that there were significant differences between treatment groups. As the dose of mung bean sprout extract increased, the percentage of spermatozoa viability also increased. This increase proved that the antioxidant content in mung bean sprout extract can inhibit oxidative stress triggered by MSG. Mung bean sprouts have the potential as a therapeutic ingredient to increase spermatozoa viability.